Pengaruh Tutor Teman Sebaya Terhadap Kemampuan Berpikir Kritis Siswa Kelas XI di SMAN 9 Kota Jambi - Wuriyanti, Martina; Sari, Pratiwi Indah (SJEE (Scientific Journals of Economic Education), 2026)
This study aims to determine the influence of peer tutoring on the critical thinking skills of class XI students of SMAN 9 Jambi City in economics subjects. The research method used in this study is a quantitative method of quantitative research with a descriptive analysis research design and simple regression, with research subjects totaling 125 students using proportional random sampling techniques. The results of the study indicate that there is an influence of peer tutoring on the critical thinking skills of class XI students at SMAN 9 Jambi City. The results of the study obtained that t count> t table, namely 8.899> 1.6573 with a large b constant value of 29.265 and an x value of 0.844. The simple regression equation obtained is Y = a + bx with Y = 29.265 + 0.844x with a t count = 8.899. Where if peer tutoring increases by 0.844% then critical thinking skills increase by 1% conversely, if peer tutoring decreases by 0.844% then critical thinking decreases by 1%.